Migação dos choques nos termos de troca sobre o câmbio - Gebrim, Gabriel Santiago (2016)
This paper analyzes if international reserves can reduce the effects of terms of trade shocks over the Exchange rate in Brazil. For this matter, an expansion of the model proposed by Aizeman e Riera-Critchon (2008) was developed for the Brazilian reality. The paper uses quartely data from 1972 to 2015. The results shows evidence that the active managment of international reservas can smooth the effect of terms of trade shocks over the Exchange rate and current account.